Leaves of Indoor Ornamentals Are Biodiversity and Functional Hotspots for Fungi - Mahnert, Alexander; Ortega, Rocel Amor; Berg, Christian; Grube, Martin; Berg, Gabriele (Frontiers in Microbiology, 2018)
Leaf-inhabiting fungi are an important, but often overlooked component of molecular biodiversity studies. To understand their diversity and function in relation to plant species and climate, the phyllospheres of 14 phylogenetically diverse ornamental plant species were analyzed under different controlled greenhouse conditions. We found unexpectedly high fungal diversity (H’ = 2.8 - 6.5), OTU numbers (449-1050) and abundances (103-106 CFU cm-2 leaf surface) associated with all plants studied indoors. Despite experimental limitations, the composition of fungal communities were inclined towards a plant species-dependent pattern compared to the ambient climatic variables. Most detected fungi were patho- and saprotrophs showing a yeast-like growth morphology and were associated to the groups of endophytes and potential plant pathogens in a plant species-specific manner. A representative strain collection showed that 1/3 of the tested fungi (mainly Penicillium, Cladosporium, and Cryptococcus spp.) was able to inhibit mycelial growth and 2/3 inhibit sporulation of the plant pathogen Botrytis cinerea by the production of antifungal volatile organic compounds (VOCs) completely. This study indicates that plant leaves harbor a stable phyllosphere fungal diversity in diverse microclimates and enrich distinctive functional guilds.